TIK DALAM MASA PANDEMI - Nurwahid, Muhammad Salman; Aprilliantoni, Aprilliantoni (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The COVID-19 epidemic has drastically altered society's way of life, demonstrating the significance of ICT in supporting a variety of facets of human existence. This study focuses on how the pandemic affects ICT use, particularly in social communication, the workplace, education, and health. The study methodology employed is a qualitative one that includes in-depth interviews with IT specialists and a review of the literature. Information was gathered from books, journal papers, interviews, and other sources. The study's findings indicate that the primary substitute for the current educational system is online learning. However, issues with unreliable internet access and device constraints plague online learning. Despite worries about data security, telemedicine is becoming more and more common in the healthcare industry, providing safe remote health consultations. Yet, despite worries about data security, the use of telecommuting and working from home has increased because to technology like VPNs and video conferencing software. A lot of companies are now using e-commerce, which is expanding quickly. Social communication is sustained through instant messaging apps and social media. This study indicates that ICT is crucial for preserving social connection and productivity throughout the epidemic. It is also anticipated that this research will advance when the pandemic is over.